Penerapan Metode Fuzzy Logic dalam Estimasi Waktu Produksi Konveksi Kaos Massal - Dimas Abisono Punkastyo; Azzahra Nur Oktavia (Teknik Informatika Universitas Pamulang, 2026)
The process of estimating production time in the garment manufacturing industry is generally performed manually and relies on experience, making it subjective and often causing discrepancies between estimated and actual completion times. This study aims to design and develop a web-based production time estimation system by applying the Fuzzy Logic Mamdani method to provide more objective and measurable estimates. The system processes production variables such as the number of products, design complexity, number of workers, and number of design sides using the Mamdani fuzzy inference mechanism to obtain estimated production times. System testing was conducted using Black Box Testing to ensure all features function according to specifications, and accuracy evaluation was performed using Mean Absolute Percentage Error (MAPE). The results show that the system can provide production time estimates with an average MAPE of 6.73%, categorizing it as highly accurate and suitable for supporting decision-making. Therefore, this web-based system proves to assist garment manufacturers in calculating production time quickly, objectively, and accurately.